Lower third molar fused with a supernumerary tooth: diagnosis and treatment planning using Cone-Beam Computed Tomography - FERREIRA-JÚNIOR,Osny (2014)
Fusion is the union of two developing dental germs, resulting in a single large dental structure. It involve two normal dental germs or the germ of a normal tooth with a germ of a supernumerary one. Supernumerary teeth are additional teeth of the normal series which may occur in any region of the dental arch, althoug they are more common in the maxilla than in the mandible. This article presents a case of fusion between a third molar and a supernumerary tooth, in which a surgical intervention was carried out, with the objective of removing the dental elements. The panoramic radiography was complemented by the Donovan´s radiographic technique, but because of the proximity of the dental element to the mandibular ramus, it was not possible to have a final fusion diagnosis. Hence, the Cone-Beam Computed Tomography which provides precise three-dimensional information, was used to determinate the fusion diagnosis and also to help in the surgical planning.